Social transformation through affirmation of human dignity in a faith-based organisation - Mellows, Susan; Bowers du Toit, Nadine (Stellenbosch Theological Journal, 2023)
The contribution towards poverty upliftment in South Africa by a faith-based organisation (“FBO”) which practises integrated spirituality has not been clearly ascertained. Based on a case study conducted within the field of Theology and Development, it can be suggested that an FBO, through the practice of holistic spirituality, can empower people who are economically deprived, by assisting them to activate their agency, as their human dignity is affirmed, and vocation recovered. In drawing on resources relating to its faith dimension, including theological concepts such as the imago Dei, shalom and the kingdom of God, in the instance of the study reported on, the role of the FBO can be valuable in development work. The conclusion drawn is that recent interest in inclusion of spirituality within development discourse is to be welcomed as a beneficial addition in striving towards social transformation.